Application of Lignin as Adsorbent for Silver (Ag) and Copper (Cu) on Electroplating Waste in Kota Gede - Prakoso, Nurcahyo Iman (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2018)
Lignin was a component of wood and always eliminated by chemical processing in many industries. On the other hand, oil palm bunches were the waste of palm oil industry, where that also containing high lignin. This study used lignin from residual waste of palm oil industry as biomass to adsorb silver (Ag) and copper (Cu) metal that is contained in electroplating waste by looking at lignin mass ratio, temperature and time in order to obtain optimal adsorption condition. The mass variations used were 100 mg, 200 mg, 300 mg, 400 mg, and 500 mg. While for the variation of contact time were 2 hours, 3 hours, 4 hours, 5 hours, 6 hours. For temperature variations were 30 Â°C, 40 Â°C, 50 Â°C, Â Â andÂ 60 Â°C. The results showed that the most optimal lignin mass ratio in adsorbing silver and copper metals was 200 mg/ 50 mL. While the most optimal contact time were 4 hours for Ag and 2 hours for Cu. For the most optimum temperature in adsorbing Ag metal at 50 Â°C and for Cu metal at 30 Â°C.